Lançamento de foguetes pet no contexto do ensino médio: um convite para o aprendizado da composição de movimentos e da terceira lei de Newton por um sistema de massa variável - Oliveira, Paulo Sérgio Prado de (2022)
In the last decades of the end of the 20th century and beginning of the 21st century, teaching practices that deal with contemporary themes that involve social issues and reflections on the part of students have been increasingly recommended in the school curriculum and, to a large extent, are not restricted to an area of knowledge. With the discussion of a National Curricular Common Base (BNCC), themes that involve multiple disciplines in a transversal way, gained prominence and proved to be important for the formation of new citizens. In this context, the objective of this work was to build a didactic sequence aimed at launching PET rockets propelled by compressed air and water with the participation in all stages of construction, from the rocket launcher to the rocket itself. With this, the student can visualize and discuss, in an experimental way, questions related to oblique motion, Newton's Third Law, launches and topics related to real rockets, such as the space race and technologies, fuels and the environment, climatic conditions for the launch, between others. For this purpose, assembly kits and instructions scripts were prepared, as well as explanatory videos and guides for data collection. The development of the activity was initially proposed in person, but due to the health restrictions adopted due to the pandemic caused by the SARS-COV 2 virus (Covid 19), much of the application was done remotely using computer resources, such as online classes. -line, launch simulators and video editors. An initial questionnaire was applied in order to verify the students' level of knowledge on the topic. After the launcher and rocket construction stage, the students, organized into groups, performed the launches in non-formal space and the collected data were used to calculate the launch speed, the maximum height reached, the propellant ejection speed. and rocket thrust. After the necessary calculations, the students compared the values obtained experimentally with those found via simulators, such as the PhET-Colorado application. Finally, the students collected the mass of the rocket, before and after the launch, consolidating the theme of composition of movement with activities that interconnect the experiments carried out and the theoretical part.